IC50 and Cell Viability of Combination of Ethanol Extract Moringa oleifera Leave (EEMo) and Ethanol Extract Carica papaya Leave (EECp) on Breast Cancer Cells - Nuni Rismayanti Nurkalbi; Aryadi Arsyad; Ika Yustisia; Yulia Y Djabir (Health Notions, 2021)
This study aims to find out IC50 and Cell Viability of the combination of ethanol extract leaves of Moringa oleifera (EEMo) and ethanol extract leaves of Carica papaya (EECp) on the growth of MCF-7 breast cancer cells culture. It was conducted in a true experimental laboratory using post-test only control group design method. The study showed that the effect of extract combination for MCF-7 Cell by using series concentration like 0, 20, 40, 80 and 160 µg/mL for 48, 72, and 96 hours with a cell density of 5x103 after giving WST assay there is a decrease in the number of cell viability. Inhibition concentration of MCF-7 cell culture was also indicated by the IC50 value which was included in the very strong category with details of each extract combination with 1:1 comparison the IC50 value is 12.02 µg/mL. Keywords: extract combination; IC50; cell viability, MCF-7